Postural control in 13-year-old soccer players - Biec, E.; Kuczynski, M. (European Journal of Applied Physiology, 2010)
To evaluate the effect of early systematic soccer training on postural control we measured center-of-pressure (COP) variability, range, mean velocity and frequency in bipedal quiet stance with eyes open (EO) and closed (EC) in 44 boys aged 13 (25 boys who practiced soccer for 5-6 years and 19 healthy boys who did not practice sports). The soccer players had better stability, particularly in the medial-lateral plane (M/L); their COP variability and range were lower than in controls in both EO (p < 0.05) and EC (p < 0.0005) condition indicating that the athletes were less dependent on vision than non-athletes. Improved stability of athletes was accompanied by a decrease in COP frequency (p < 0.001 in EO, and p < 0.04 in EC) which accounted for lower regulatory activity of balance system in soccer players. The athletes had lower COP mean velocity than controls (p < 0.0001 in both visual condition), with larger difference in the M/L than A/P plane (p < 0.00001 and p < 0.05, respectively). Postural behavior was more variable within the non-athletes than soccer players, mainly in the EC stances (p < 0.005 for all COP parameters). We conclude that: (1) soccer training described was efficient in improving the M/L postural control in young boys; (2) athletes developed specific postural strategies characterized by decreased COP frequency and lower reliance on vision.